Security bid auctions for agency contracts - Byoung Heon Jun; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
A principal uses security bid auctions to award an incentive contract to one among several agents, in the presence of hidden action and hidden information. Securities range from cash to equity and call options. 'Steeper' securities are better surplus extractors that narrow the gap between the two highest valuations, yet reduce effort incentives. In view of this trade-off, the generalized equity auction that includes a (possibly negative) cash reward to the winner tends to outperform all other auctions, although it cannot extract the entire surplus implement efficient effort. Hence, profit sharing emerges without risk aversion or limited liability.
urn:nbn:de:bvb:19-epub-13183-5
Keywords: D21; D43; D44; D45; 330; Auctions; agency problems; licensing; innovation; mechanism design; Erfolgsbeteiligung; Aktienoption; Auktionstheorie; Prinzipal-Agent-Theorie; Anreizvertrag; Theorie